Employee Learning Orientation, Job Security, and Job Engagement: The Mediating Role of Employee Loyalty Among Non-Permanent Employees In The Hospitality Sector - Nanda Wulandari; Ayu, Ade; Meidiani, Indah; Muhammad Siddiq, Dedi (Dinasti Publisher, 2024)
Work engagement plays a crucial role as it involves sentiments beyond job satisfaction, such as genuine dedication, pride, dignity, and fostering loyalty among employees. Employee work engagement can result in a workforce oriented towards employee learning and maintaining employee job security, which is beneficial for the organization. This study aims to examine the extent to which employee loyalty intervenes among non- permanent employees in mediating the relationship between employee learning orientation and job security towards employee work engagement. The respondents in this study are non- permanent employees in the hospitality sector, with data obtained from a survey of both population and sample of non- permanent employees, totaling 200 respondents from 9 hotels. The study utilizes multiple correlation analysis, validity tests, reliability tests, and determination analysis test by comparing them to the table. The data analysis results indicate that using the methods of multiple correlation analysis, validity tests, reliability tests, and determination analysis test this study found that the perception of employee loyalty support in mediating the relationship between employee learning ability and non- permanent employee job security in the hospitality sector both have a positive and significant relationship with work engagement.